Pronominal Placement in the Brazilian Portuguese of Nova Iguaçu: What Does the Empirical Data Reveal From the Comparison Between Speech and Writing? (Revista de Estudos da Linguagem, 2024)
This research investigates the variable phenomenon of pronoun clitic position in simple lexemes, based on speech and writing samples collected in Nova Iguaçu (RJ). Adopting the theoretical framework of Variationist Sociolinguistics, we intend to determine the social and linguistic factors that trigger the use of proclisis over the use of ênclisis in oral and written forms of language, as well as to recognize which are the most frequent traditional and non-traditional proclisive elements together with the use of proclisis. According to the data analysis, it was possible to bring out the following statements: (a) proclisis proved to be more productive than ênclise, especially in oral language; (b) the proclising element type factor group was the group that most influenced pronominal collocation in both language modalities (oral and written); (c) the speaker’s schooling factor group, although it did not control in written language, was also shown to be relevant for pronominal placement; and (d) some other linguistic factors were shown to be relevant, however, divergently in the spoken and written data, showing that their influences depend on the linguistic context in question.